Problems of life and mind: first series : The foundation of a creed - Lewes, George Henry (Houghton, Mifflin, 1879)
v. 1. The method of science and its application to metaphysics. The rules of philosophizing. The limitations of knowledge.--v. 2. The principles of certitude. From the known to the unknown. Matter and force. Force and cause. The absolute in the correlations of feeling and motion.Appendix: Imaginary geometry and the truth of axioms. Lagrange and Hegel: the speculative method. Action at a distance.